The Implementation and Inhibiting Factors of Using Qris as a Muamalah Transaction System in Islamic Boarding Schools - Azmil Zamara Yasmin; Muhammad Fahmul Iltiham; Muhammad Mukhsinin Syu'aibi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasing access to digital financial technology has driven the adoption of non-cash payment systems in various traditional sectors, including Islamic educational institutions. This study aims to determine and describe the implementation and inhibiting factors of using Quick Response Code Indonesian Standard (QRIS) as a muamalah transaction system among students at Pondok Pesantren Ngalah, Purwosari, Pasuruan. This research applies a qualitative descriptive approach using the Miles and Huberman model for data analysis. Data were gathered through in-depth interviews, direct observations, and documentation. The results indicate that QRIS has been implemented well in daily transactions such as buying food, drinks, stationeries, and paying for printing services, driven by its perceived usefulness, efficiency, and ease of use. From a sharia perspective, the implementation of QRIS complies with muamalah principles including transparency, clarity of transactions (bayan), and mutual consent (an-taradhin), free from elements of riba (usury), gharar (uncertainty), and maysir (gambling). However, the study identifies several inhibiting factors, including an unstable internet connection in pesantren areas, low digital literacy among some users causing fear of transactional errors, deep-rooted habits of using cash, and a lack of specific educational programs on sharia digital muamalah that leads some students to equate QRIS with online loans or paylater features. This paper concludes that while digital payment adoption is growing within Islamic educational institutions, enhancement of digital infrastructure and sharia financial literacy remains critical.